'Take us with you Scotland'? Post-Referendum and Post-Election Reflections from the North East Of England. Issue 4 (November 2015) - Shaw, Keith
Abstract : This article examines the different reactions in North East England to the results of both the Scottish Independence Referendum in September 2014 and the General Election in May 2015. It outlines how the region's relief at the 'No' vote quickly gave way to traditional fears – once the Smith Commission had reported – that a more powerful Scotland would undermine economic fortunes just south of the border. To fear of a more powerful 'neighbour' was added a noticeable level of political hostility towards the SNP in particular, as the virtual wipe out of Labour MP's in Scotland in May's General Election has left many North East Labour politicians (in the party's one remaining heartland) uncertain and anxious about their own political future. However, the North East of England has also tried to harness the referendum outcome in more practical ways. In the first instance, using it to strengthen its own case to Westminster for greater devolved powers and, secondly, to explore opportunities for a more collaborative, cross-border approach to economic development. The article concludes by contrasting the growing disjunction between the increasingly sympathetic and supportive views of North Easterners towards what's happening in Scotland, and the hostile views of many North East Labour politicians. Those advocating that the region should work with the Scots, and gain the support of more powerful SNP group in Westminster for greater devolution in England, have a real challenge to overcome the hostile views of North East politicians towards both nationalism and nationalists.